Muscles in the Movies : Perfecting the Art of Illusion - Fair, John D.; Chapman, David L., 1948- (Book collections on Project MUSE., 2020)
"This book tells the story of how filmmakers use and manipulate the appearance and performances of muscular men and women to enhance the appeal of their productions. The authors show how this practice, deeply rooted in western epistemological traditions, evolved from the art of photography through magic lantern and stage shows into the motion picture industry, arguing that the sight of muscles in action induced a higher degree of viewer entertainment. From silent film star Maciste to Dwayne "The Rock" Johnson, muscular actors appear capable of performing the miraculous, and with the aid of stunt doubles and filming contrivances, they do. By such means, muscles are used to perfect the art of illusion, inherent in moviemaking from its earliest days"--